Creativity, Mating, and Reproductive Successes Outside the WEIRD World. Issue 3 (3rd July 2021) - Lebuda, Izabela; Sorokowski, Piotr; Groyecka-Bernard, Agata; Marczak, Michalina; Gajda, Aleksandra; Jankowska, Dorota M.; Karwowski, Maciej
ABSTRACT: This study provides an empirical test of the relationship between creative potential, mating, and reproductive success in a sample using natural methods of fertility control: the Meru tribe living in the regions of Laare and Mutuati in Kenya. The participants ( N = 133; 65 females) solved a figural creativity test (the Test of Creative Thinking – Drawing Production, TCT-DP) and provided information about the number of spouses, children, length of their schooling, as well as wealth. Analyses demonstrated that creative potential negatively predicted the number of offspring, but this relation was fully mediated by the number of spouses: more creative people more often stayed single and did not have offspring. The theoretical consequences of these findings are discussed in light of the evolutionary psychology of creativity.